Analisis Dampak Pengembangan dan Implementasi Kurikulum MBKM Terhadap Kepuasan Mahasiswa FIP UNIKAMA - Denna Delawanti Chrisyarani; Sri Rahayu; Yulianti Yulianti; Ika Meviana; Ayu Asmah; Iskandar Ladamay (Jurnal Bidang Pendidikan Dasar, 2022)
The purpose of this study was to analyze the internal student satisfaction of Study Programs within the Faculty of Education. This research is a quantitative descriptive study with a survey method using a questionnaire as a data collection tool. The survey results show that the average student satisfaction in the Faculty of Education, Universitas PGRI Kanjuruhan Malang shows a very good category. Tangibles dimension has an average percentage of 40.33% with a very good category. Responsiveness with an average percentage of 57.72%, Reliability with an average percentage of 50.95%, and Empathy with the highest 75.4%. Based on the results of data processing, it is concluded that the overall level of student satisfaction based on the dimensions of service satisfaction on the implementation of MBKM is classified as very good